Anisotropic quark stars in f(R, Lm,T) gravity - Tangphati, Takol; Sakalli, Izzet; Banerjee, Ayan; Pradhan, Anirudh (Iop Publishing Ltd, 2025)
We investigated the impact of gravity on the internal structure of compact stars, expecting this theory to manifest prominently in the high-density cores of such stars. We considered the algebraic function , where alpha represents the matter-geometry coupling constant. We specifically chose the matter Lagrangian density to explore compact stars with anisotropic pressure. To this end, we employed the MIT bag model as an equation of state. Subsequently, we numerically solved the hydrostatic equilibrium equations to obtain mass-radius relations for quark stars (QSs), examining static stability criteria, adiabatic index, and speed of sound. Finally, we used recent astrophysical data to constrain the coupling parameter alpha, which may lead to either larger or smaller masses for QSs, compared to their counterparts in general relativity.
Keywords: $f(R, L_m,T) $ gravity; anisotropic quark stars; compact stars; MIT bag model; matter-geometry coupling